HERDING BEHAVIOR, EXPERIENCED REGRET DAN KEPUTUSAN INVESTASI PADA BITCOIN - Edi Pranyoto; Susanti Susanti; Septiyani Septiyani (Jurnal Bisnis Darmajaya, 2020)
The objective of this research was to determine the effect of the herding behavior and the experienced regret on the investment decision. The type of this research was quantitative research. The data collecting technique used in this research was distributing questionnaires. The sampling technique used in this research was the snowball sampling technique. The number of samples used in this research was 100 investor of bitcoin. The data analyzing technique used in this research was the multiple linear regression analysis. The result of this research showed that the herding behavior had no significant effects on the investment decision; moreover, the experienced regret had a positive and significant effect on the investment decision. It meant that the investors rationally received and analyzed information well in bitcoin because they were not affected by the other investors and did not follow the market situation. In addition, the experienced level of investor regret was considered higher on the condition that the investment decision was also higher because they had enough experience in making the investment decision.  Keywords — Herding Behavior, Experienced Regret, Investment Decision, Bitcoin